Localización óptima de reconectadores con criterios de confiabilidad en un alimentador real de medio voltaje de un sistema eléctrico de distribución. - Silva Poaquiza, Marco Vinicio (2022)
The growing demand and importance of electricity today means that the Distribution Companies are constantly developing improvements in the electrical networks, seeking to guarantee a continuous, reliable and quality service to the end user. Distribution systems are made up of a set of components, including medium voltage feeders, which in turn contain cutting and protection equipment such as the so-called automatic reclosers; To improve the reliability of a medium voltage feeder, this equipment is used precisely to minimize the duration (SAIDI) and the frequency (SAIFI) of service interruptions. Hence the need to define an optimization method for the location of reclosers based on an improvement in reliability in a real medium voltage feeder of an electrical distribution system. For which the specialized literature on optimization recommends the use of a heuristic methodology known as Genetic Algorithms, mainly for exploring the space of solutions in multiple directions. Genetic algorithms mimic biological evolution, it consists of three stages: selection, crossing and mutation, thus obtaining a new improved population. The OpenDSS and Matlab software tools are used for the development of the modeling - simulation and interface - optimization algorithms, respectively. The result obtained is satisfactory, since the optimal location of the reclosers was obtained with an improvement in the reliability of the system, which was chosen from a set of possible solutions provided by the methodology.